How are work-related characteristics linked to sickness absence and presenteeism? Theory and data - Daniel Arnold; Marco De Pinto (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper investigates how changes in work-related factors affect workers' absence and presenteeism behavior. Previous studies (implicitly) assume that there is a substitutive relationship, i.e. a change in a work-related factor decreases the level of absence and simultaneously increases presenteeism (or vice versa). We set up a theoretical model in which work-related characteristics not only affect a worker's absence decision but also the individual-specific sickness definition. Since workrelated factors affect presenteeism through these two channels, nonsubstitutive relationships between absence and presenteeism are also conceivable. Using European cross-sectional data, we find only few substitutive and complementary relationships, while the bulk of the work-related characteristics is related only to one of the two sickness states.
Keywords: J22; J28; I1; M50; 330; sickness absence; presenteeism; annual duration; workrelated characteristics; health at work